2022
DOI: 10.1213/ane.0000000000005862
|View full text |Cite
|
Sign up to set email alerts
|

Placenta Accreta Spectrum Disorders: Knowledge Gaps in Anesthesia Care

Abstract: Placenta accreta spectrum (PAS) disorder is a potentially life-threatening condition that can occur during pregnancy. PAS puts pregnant individuals at a very high risk of major blood loss, hysterectomy, and intensive care unit admission. These patients should receive care in a center with multidisciplinary experience and expertise in managing PAS disorder. Obstetric anesthesiologists play vital roles in the peripartum care of pregnant patients with suspected PAS. As well as providing high-quality anesthesia ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…In a survey of obstetric anesthesia experts based at multiple academic centers, 100% of respondents reported that PAS surgeries were staffed by an attending obstetric anesthesiologist. 5 In the event of an emergency cesarean hysterectomy, the assigned anesthesiologist may benefit from the use of a standardized cesarean hysterectomy anesthetic protocol or checklist (►Table 1). The use of a protocol or checklist may standardize care, particularly when delivery is necessary outside of normal working hours with providers who are not part of the primary care team.…”
Section: Staffing and Team Communicationmentioning
confidence: 99%
See 3 more Smart Citations
“…In a survey of obstetric anesthesia experts based at multiple academic centers, 100% of respondents reported that PAS surgeries were staffed by an attending obstetric anesthesiologist. 5 In the event of an emergency cesarean hysterectomy, the assigned anesthesiologist may benefit from the use of a standardized cesarean hysterectomy anesthetic protocol or checklist (►Table 1). The use of a protocol or checklist may standardize care, particularly when delivery is necessary outside of normal working hours with providers who are not part of the primary care team.…”
Section: Staffing and Team Communicationmentioning
confidence: 99%
“…The use of a protocol or checklist may standardize care, particularly when delivery is necessary outside of normal working hours with providers who are not part of the primary care team. 1,5 We also recommend a preoperative briefing between all PAS team members to confirm the perioperative plan and contingency plans in the event of major bleeding, surgical injury, or major hemodynamic compromise. Preoperative briefings can improve patient safety, operating room efficiency, and team communication.…”
Section: Staffing and Team Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no consensus on the optimal anaesthetic technique and multiple clinical and institutional factors may influence these choices [67]. The key to successful management is anticipating the need for rapid and massive transfusion.…”
Section: Placenta Accreta Spectrummentioning
confidence: 99%